TOPOLOGICAL STRUCTURE AND MOBILITY OF THE MECHANISMS USED IN CAR MECHANICAL JACKS - Viorica VELIȘCU; Dan MESARICI,; Păun ANTONESCU (Fiabilitate şi Durabilitate)
This paper presents a structural analysis of the mechanism of high topological type jack - screw and translator rectilinear- patina and mobility mechanism analysis using various generally applicable formulas.